Human cryptosporidiosis caused by Cryptosporidium tyzzeri and C. parvum isolates presumably transmitted from wild mice - Rasková, Veronika; Kvetonová, Dana; Sak, Bohumil; McEvoy, John; Edwinson, Adam; Stenger, Brianna; Kvác, Martin (Journal of clinical microbiology, 2013)
We report a case of severe human cryptosporidiosis caused by Cryptosporidium tyzzeri and C. parvum with an unusually high frequency of liquid stools. Wild mice were the most likely source of infection, demonstrating the potential for wild-mouse-borne Cryptosporidium to infect humans and highlighting the health risks associated with synantropic rodents.
Keywords: protozoální DNA; Zoonoses; kryptosporidióza; Sequence Analysis, DNA; Cryptosporidiosis; Animals, Wild; sekvenční analýza DNA; molekulární sekvence - údaje; zoonózy; Adult; divoká zvířata; dospělí; DNA, Protozoan; Animals; lidé; ženské pohlaví; Humans; zvířata; myši; Cryptosporidium; Molecular Sequence Data; Mice; Female